2012
DOI: 10.2500/ajra.2012.26.3724
|View full text |Cite
|
Sign up to set email alerts
|

Corelationship between Matrix Metalloproteinase 2 and 9 Expression and Severity of Chronic Rhinosinusitis with Nasal Polyposis

Abstract: These results suggested up-regulation of MMP-9, and MMP-2 in gland and surface epithelium, respectively, were characteristic of NPs. Therefore, patients with allergy will exhibit greater MMP-2 and -9 positivity. However, the MMP-2 and -9 expression intensity was not correlated with the severity of CRS with nasal polyposis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 37 publications
2
25
1
2
Order By: Relevance
“…No significant correlation has been observed between MMP gene expression and sinonasal computed tomography (CT) scan extension [33]. This confirmed a previous report in which MMP-2 and MMP-9 expression intensity was not correlated with the endoscopic or radiological severity of CRSwNP [34].…”
Section: Metalloproteinasessupporting
confidence: 89%
“…No significant correlation has been observed between MMP gene expression and sinonasal computed tomography (CT) scan extension [33]. This confirmed a previous report in which MMP-2 and MMP-9 expression intensity was not correlated with the endoscopic or radiological severity of CRSwNP [34].…”
Section: Metalloproteinasessupporting
confidence: 89%
“…Fibroblasts also secrete MMPs that may contribute to tissue destruction [13]. Expression levels of MMPs have been found to be elevated in nasal polyp tissues compared to control tissues and play important roles in the formation of nasal polyposis [14], [15]. However, the role of LPS-induced pro-inflammatory cytokines and MMPs in nasal polyp-derived fibroblasts (NPDFs) has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Increased MMP-9 expression has been reported in NPs of patients with recurrent CRSwNP compared with nonrecurrent CRSwNP patients and controls [75]. However, another study reported no significant differences in MMP-9 immunoreactivity between recurrent and nonrecurrent NPs, and MMP-9 immunoreactivity did not either correlate with NP grade and CRSwNP severity [76].…”
Section: Remodeling Factorsmentioning
confidence: 95%
“…and resp. CRSwNP [76] Periostin CRS+AERD (130) Serum ELISA ↑ In patients with high CT score a vs. patients with low CT score [77] Molecules involved in edema VEGF-B…”
Section: Ihqmentioning
confidence: 98%